Control Active Magnetic Bearing with Backsteping Silding Mode Control - Giang, Hong Quan; Nguyen, Danh Huy; Nguyen, Tung Lam; Giang, Hong Bac (Old Journal, 2018)
In active magnetic bearing systems, the magnetic force is proportional to the square of the current and inversely proportional to the square of the distance gap between the stator and rotor. In order to design the control algorithm, we must linearize this relationship. Control algorithms ensure good quality, exactly as designed only at the point of operation. This paper proposes a solution designed to help implement the controller without linearization. The proposed algorithm is combined of backstepping and sliding mode control. In addition, an observer is integrated to estimate load variation. The obtained result was verified with simulation Matlab/Simulink. Simulation results prove the effectiveness of the control structure.